2021
DOI: 10.1142/s0129183121501643
|View full text |Cite
|
Sign up to set email alerts
|

Synchronization of time-varying coupled complex networks via adaptive pinning control

Abstract: Pinning synchronization of complex networks with two different kinds of time-varying coupling are studied in this paper. Inner coupling of the state variables and outer coupling in the complex network are taken into consideration. Based on the Lyapunov function theory, some general criteria and a simplified corollary for ensuring network synchronization are proposed. Linear pinning controllers, adaptive pinning controllers and adaptive coupling strength are designed for achieving complex network time-varying s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…In the field of pinning control research, a lot of research has been done by many scholars on the problem of pinning control selection strategy. Lin and Wang [5]studied the problem of local and global synchronization for pinning control of complex networks, and the paper gives the conclusion that even with a random node selection strategy, if enough nodes are controlled for a network, the network can be synchronized. Wang and Chen [6] choose a scale-free network as an example to demonstrate that pinning nodes with large degree can make the complex network reach synchronization faster, and after comparison, it is found that the degree-based control strategy is significantly better than the random node selection strategy.…”
Section: Introductionmentioning
confidence: 99%
“…In the field of pinning control research, a lot of research has been done by many scholars on the problem of pinning control selection strategy. Lin and Wang [5]studied the problem of local and global synchronization for pinning control of complex networks, and the paper gives the conclusion that even with a random node selection strategy, if enough nodes are controlled for a network, the network can be synchronized. Wang and Chen [6] choose a scale-free network as an example to demonstrate that pinning nodes with large degree can make the complex network reach synchronization faster, and after comparison, it is found that the degree-based control strategy is significantly better than the random node selection strategy.…”
Section: Introductionmentioning
confidence: 99%